Pelatihan Penulisan Cerpen Berbantuan Kecerdasan Buatan untuk Siswa SMK Kartika di Kota Cirebon - Risma Khairun Nisya; Deden Sutrisna; Trian Pamungkas (Universitas Ekuitas Indonesia, 2025)
This project aims to train students of SMK Kartika Kota Cirebon in using artificial intelligence to synthesize short stories, while understanding its limitations in capturing symbolic meanings and signs. The training adopts Roland Barthes' semiotic perspective to delve into the symbolic meanings in short stories. The method used is a practical approach, which includes preparation, implementation, and evaluation stages. In the preparation stage, a preliminary study was conducted through questionnaires to assess students' knowledge of artificial intelligence and their interest in short story writing. The implementation stage consisted of short lectures, demonstrations of AI usage, and workshops on short story synthesis. Students were encouraged to directly use AI in generating story ideas, plots, and characters, as well as receiving constructive feedback. The training results showed an improvement in students' understanding of artificial intelligence and Roland Barthes' semiotic theory. Students were able to use AI to synthesize short stories and understand how to integrate AI outputs with their own creativity. Additionally, they were equipped with skills to publish short stories on digital platforms such as Wattpad and Fizzo. In conclusion, this training successfully enhanced the creative writing skills students, provided a deep understanding of the role and limitations of AI in short story writing, and emphasized the importance of human involvement in the literary creative process. This training is expected to equip students with relevant skills in the Society 5.0 era and open opportunities for them to contribute to the world of digital literature. Keywords: Artificial Intelligence, short story synthesis, roland barthes semiotics, training, digital publication. ————————————————————————————————————— Abstrak Proyek ini bertujuan untuk melatih siswa SMK Kartika Kota Cirebon dalam menggunakan kecerdasan buatan untuk mensintesis cerpen, sekaligus memahami keterbatasannya dalam menangkap makna simbolik dan tanda. Pelatihan ini mengadopsi perspektif semiotika Roland Barthes untuk mendalami makna simbolik dalam cerpen. Metode yang digunakan adalah metode praktik, yang meliputi tahap persiapan, pelaksanaan, dan evaluasi. Pada tahap persiapan, dilakukan studi pendahuluan melalui kuesioner untuk menilai pengetahuan siswa tentang kecerdasan buatan dan minat mereka terhadap penulisan cerpen. Praktik menggunakan teknologi Artificial intelligence (AI) seperti ChatGPT. Tahap pelaksanaan terdiri dari kuliah singkat, demonstrasi penggunaan AI, dan workshop sintesis cerpen. Siswa diajak untuk mencoba langsung menggunakan AI dalam menghasilkan ide cerita, plot, dan karakter, serta mendapatkan feedback konstruktif. Hasil pelatihan menunjukkan peningkatan pemahaman siswa tentang kecerdasan buatan dan teoritis semiotika Roland Barthes. Siswa mampu menggunakan AI untuk mensintesis cerpen dan memahami bagaimana mengintegrasikan hasil AI dengan kreativitas mereka sendiri. Selain itu, mereka juga dibekali dengan keterampilan mempublikasikan cerpen di platform digital seperti Wattpad dan Fizzo. Kesimpulannya, pelatihan ini berhasil meningkatkan keterampilan menulis kreatif siswa SMK Kartika Kota Cirebon, memberikan pemahaman mendalam tentang peran dan keterbatasan AI dalam penulisan cerpen, serta menekankan pentingnya peran manusia dalam proses kreatif sastra. Pelatihan ini diharapkan dapat membekali siswa dengan keterampilan yang relevan di era Society 5.0 dan membuka peluang bagi mereka untuk berkontribusi dalam dunia sastra digital. Kata kunci: Kecerdasan buatan, sintesis cerpen, semiotika roland barthes, pelatihan, publikasi digital.